What Can Be Found from Student Interaction Logs of Online Courses Offered in Brazil - Damasceno, André L. B.; Almeida, Cássio F. P.; Fernandes, William P. D.; Lopes, Hélio C. V.; Barbosa, Simone D. J. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Online Education has broadened the avenues of research on student behavior and performance. In this paper, we compare results in the literature about student behavior patterns and performance with an analysis of VLE logs of online courses offered in Brazil. We conducted a study exploring and analyzing data using statistical methods and machine learning techniques on a dataset provided by a Brazilian institution. Then, we compared the results of our analysis with what the literature says about student behavior and performance. Finally, we show that, although most results related to student access and course completion can also be found in courses offered in Brazil, some of our results contradict existing work, mostly when related to student performance.